Taking advantage of emergence for complex innovation eco-systems - Deborah Jane Dougherty (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
Our most pressing societal problems such as enhancing health care, developing alternate energy, revitalizing cities, and advancing the economy are complex innovation eco-systems. Complex innovation eco-systems are the next frontier in technology and innovation management, and require a transformation in strategic and institutional management so that managers can muster the staying power to persist and learn far into the future. I develop a framework to explain how participants can strategize across an entire eco-system, deal with the profound ambiguity from complexity, and handle the very long cycle times of complex innovations. Transformed strategic and institutional management combines abductive learning routines with clock-time and event-time pacing to map a portfolio of value creating opportunities far into the future. Eco-system participants use learning events, which represent available knowledge, to hypothesize new value creating opportunities and new kinds of governance structures for specific collaborations, evaluate these opportunities and governance structures by trying them out to explore assumptions and surface new possibilities, and reframe them over time.
Keywords: 650